Cutaneous Leishmaniasis in Bangladeshi Adult Male: A Case Report - Sultana, Farjana; Haque, Md Ahasanul; Afroz, Rafiya; Rahim, Abdur; Islam, Mohammad Rafiqul (Journal of Medicine, 2024)
Abstract not available J MEDICINE 2024; 25: 98-99